2015
DOI: 10.1371/journal.pone.0118704
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Thrombin: A Novel Marker of Glomerular Inflammation for the Diagnosis of Crescentic Glomerulonephritis (Prospective Observational Study)

Abstract: BackgroundCrescentic glomerulonephritis (CresGN), an uncommon rapidly progressive disease, is characterized by severe glomerular inflammation with fibrin deposition. The lack of specific CresGN biomarkers delays diagnosis and threatens life. Because fibrin deposits in CresGN glomeruli indicate thrombin generation, we hypothesized that thrombin is excreted in urine and is a specific CresGN biomarker.MethodsWe measured urinary thrombin activity in 200 untreated patients (17 with CresGN, 183 with primary glomerul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
(35 reference statements)
0
10
0
1
Order By: Relevance
“…Given its high sensitivity and selectivity, this UPSS could potentially be used to detect early biomarkers in complex body fluid in chronic diseases such as cancer. For example, thrombin‐specific UPSS could be used for accurate detection of urinary thrombin, which was found to be present in patients with glomerulonephritis or lupus nephritis . Also, the UPSS possesses potential in monitoring the quality and safety of drinking water portably and rapidly.…”
mentioning
confidence: 99%
“…Given its high sensitivity and selectivity, this UPSS could potentially be used to detect early biomarkers in complex body fluid in chronic diseases such as cancer. For example, thrombin‐specific UPSS could be used for accurate detection of urinary thrombin, which was found to be present in patients with glomerulonephritis or lupus nephritis . Also, the UPSS possesses potential in monitoring the quality and safety of drinking water portably and rapidly.…”
mentioning
confidence: 99%
“…Contrary to the previous studies, a study on THR surgery patients published in 2017 showed increased post-operative levels of F1 + 2 in plasma and urine, however, the correlation was poor and urinary F1 + 2 levels did not reflect coagulation activation post-operatively [32]. Thrombin measurements in urine have been reported for the diagnosis of crescenting glomerulonephritis [33]. Increased thrombin levels as measured by using amidolytic methods were associated with fibrin deposits in the kidney and other associated pathologic manifestations.…”
Section: Discussionmentioning
confidence: 86%
“…Here, the coagulation cascade is initiated after vascular injury, which promotes inflammation, and inflammation in turn accelerates the production of thrombin, which eventually leads to the occurrence of disease. 23 25 Simultaneously, DN is considered as a chronic inflammatory disease and is one of the most common microvascular complications of diabetes. 3 In the present study, our results showed that HIR could markedly reduce macrophage infiltration and pro-inflammatory cytokine expression in renal tissues of DN rats.…”
Section: Discussionmentioning
confidence: 99%